(untitled) (Bangladesh Journal of Medicine, 2024)
Background: Acute organophosphorus compound (OPC) poisoning is a serious public health issue, especially in the rural areas. Peradeniya organophosphorus poisoning (POP) scale was developed to assess the severity of OPC poisoning. Although degree of choline- esterase inhibition plays a key role in the severity of OPC poisoning, some other metabolic factors like dysglycemia also has an association. Cardiovascular effects of acute OPC poisoning are also common. Methods: This hospital based prospective observational study was conducted at indoor of Department of Medicine, Chattogram Medical College Hospital for six months period, from January 2020 to June 2020. Fifty patients above 12 years of age with acute OPC poisoning who fulfilled the selection criteria were selected consecutively for the study. After initial resuscitation severity of poisoning was assessed by POP scale, Random blood glucose (RBS) and 12 lead ECG was documented at the time of admission. Patients were followed up till their hospital stay to observe the outcome in terms of death, need for Intensive care unit support, and length of hospital stay. Results: The mean age was 33.33 (±11.73) (Range: 15-65) years. Male to female ratio was 1.77:1. As per the POP score 24% had mild, 54% had moderate and 22% had severe grade of poisoning. The mean Random blood glucose level was 186.05±51.44 mg/dl (range 90-288 mg/ dl) with 21 (42 %) cases having blood glucose value above 200 mg/ dl. ECG finding was abnormal in 56% of case with ST-T changes as the most common abnormality. Mortality rate was 24%. Most of the death occur in an average of 4th day of admission. POP score at the time of admission 7.5 or more had 91.7% sensitivity and 100% specificity to predict in hospital mortality. Admission Random blood glucose level of 207.9 mg/dl had 75% sensitivity and 68.4% specificity to predict in hospital mortality and morbidity. Conclusion: POP scale, glycemic changes and ECG are good markers for predicting morbidity and mortality and can be used as assessment tools for severity of poisoning and also to assess the prognosis of OPC poisoning cases. Bangladesh J Medicine 2025; 36: 50-59